PERILAKU PEDAGANG SAYUR DALAM MENGELOLA KEBERSIHAN LINGKUNGAN HIDUP - Yoni Hermawan; H.Oman Roesman (Bumi Lestari Journal of Environment, 2008)
Two variables that influenced environmental sanitation were knowledge sanitation and income of vegetable traders. The research revealed how far the correlation between the knowledge of environmental sanitation and income of vegetable traders’ vendors the way of managing the environment sanitation. The research utilized descriptive methods and correlation methods with samples of vegetable vendors in Pancasila Market, Tawang Sub-district, Tasikmalaya City. Results of this research showed that there were a positive correlation between the knowledge of environmental sanitation and income of vegetable vendors in the way of managing the environment.